Defects in functional expression of an influenza virus hemagglutinin lacking the signal peptide sequences. - Sekikawa, K (1983)
We have investigated the requirement of the signal sequence for expression of influenza virus hemagglutinin (HA). For this purpose we used a recombinant prepared from a late-region deletion mutant of simian virus 40 (SV40) and cloned influenza HA DNA; the influenza DNA was inserted into the late region of SV40 previously occupied by the deleted sequences coding for SV40 capsid proteins. A simple in-phase deletion was made in the HA DNA, resulting in loss of 11 internal amino acids from the 16 amino acid signal peptide. This deletion HA recombinant was then used to infect African green monkey kidney cells. Mutant HA was not detected on the cell surface but stably accumulated in the cytoplasm at a level similar to that of wild-type HA. NaDodSO4/polyacrylamide gel analysis of lysates from infected cells showed that mutant HA was not glycosylated. Significantly, the amount of mutant HA synthesized was not affected by tunicamycin. In contrast, wild-type HA was decreased more than 90% by tunicamycin. These findings suggest that mutant polypeptide is synthesized on free polyribosomes rather than on membrane-bound polyribosomes. The mutant HA failed to agglutinate erythrocytes, probably due to a defect directly or indirectly associated with the lack of carbohydrate side chains.